Torre Club A72 (2017)
"In general, the intervention area has problems in terms of public space, the condition of the buildings, type of buildings and activities. Currently, the potential of Caracas Avenue is not being used, although in the future, with the future metro line, the area has the potencial to be recovered and exploit all the opportunities offered by the area selected. The project is located in Barrios Unidos between 71st and 70th streets and 14th and 14th a, the lot is chosen because the problem is accentuated in the western part of Caracas and also has an interesting potential due to its proximity to 72nd street, one of it's fronts faces Caracas, the relation with Transmilenio-s trunk lines, the future metro line and the current flow of people and vehicles that the sector is given. Due to the conditions of the place and the analysis carried out, it is found that in the corners of the intervention sector there is great activity in terms of uses and flows of people but in the section between the two corners there is a fragmentation of activity that gives the perception of insecurity and abandonment once the activities cease. For the above, a housing building is proposed since on the one hand it generates more night and weekend activity, and on the other, the relationship between the dwelling and the users allows to revitalize the area, generating a sense of permanence that pretends improve the face of the Caracas taking advantage of all the opportunities it offers. Since the project must respond to the conditions of the place, propitiate the conditions for the program to be possible and respond to the urban life that occurs in the intervention sector, a tower of apartments is proposed on a trading platform that allows the development of urban life in the first floor and responds to the commercial character of the Caracas as to the neighborhood character of the Alcázares in the back of the block."--Tomado del Formato de Documento de Grado